THE "GREEN" ECONOMY OF NEW UZBEKISTAN: KEY TRENDS FOR COMPARATIVE ANALYSIS - Muitov Davron Sobirovich; Akhmedova Shakhrizoda Anvarovna (Scholar Express Journals, 2024)
This article explores Uzbekistan's transition to a green economy, emphasizing the country's commitment to sustainable development through a range of environmental reforms and initiatives. The discussion highlights key strategies, including the development of renewable energy sources, such as solar and wind power, the modernization of transportation systems through the introduction of electric buses and railway electrification, and the implementation of water-saving technologies in agriculture. The adoption of the National Strategy for Transition to a Green Economy until 2030 and active participation in international agreements, such as the Paris Agreement, underscore Uzbekistan's alignment with global sustainability standards. The article also examines the challenges posed by climate change, including reduced water resources and agricultural productivity, and emphasizes the need for international cooperation and investment. Key measures discussed include the redistribution of financial resources toward eco-friendly sectors, institutional support for environmental reforms, and the integration of UNEP recommendations. By analyzing national and international practices, the article underscores Uzbekistan's significant progress in harmonizing economic growth with environmental protection, positioning the country as a regional leader in sustainable development.
Keywords: Green economy; Uzbekistan; sustainable development